Intellectual Capital Profiles: An Examination of Investments and Returns* - Youndt, Mark A.; Subramaniam, Mohan; Snell, Scott A. (Journal of Management Studies, 2004)
ABSTRACT Using data collected from executives in 208 organizations, this study takes a configurational approach to examine how human, social, and organizational capital coexist to form distinct intellectual capital profiles across organizations. We then examine how investments in human resource management (HRM), information technology (IT), and research and development (R&D) differ across these intellectual capital profiles and investigate differences in financial returns and Tobin's q between the profiles. Results indicate that a relatively small group of superior performing organizations exhibit high levels of human, social, and organizational capital. Most firms, however, tend to focus primarily on only one form of intellectual capital, and a small group of underperforming organizations have very low levels of all three types of intellectual capital. At a general level, HRM and IT investments appear to influence intellectual capital development more than R&D investments. More specifically, HRM investments tend to be higher in firms with profiles high in human and social capital, while IT investments are stronger in firms with profiles high in social capital. Further, HRM, IT, and R&D investments are all very high in the group of superior performing organizations that have high levels of human, social, and organizational capital.